The Clinical Features of Comorbid Pediatric Bipolar Disorder in Children with Autism Spectrum Disorder - Sapmaz, Dicle; Baykal, Saliha; Akbaş, Seher (Journal of autism and developmental disorders, 2018)
The aim of this study was to describe clinical features of PBD comorbidity in children with ASD. Forty children with ASD and PBD aged 6–18 years, and 40 age- and sex-matched ASD subjects with no affective episodes were included in the study. Autism Behavior CheckList, Abberant Behavior CheckList, and Young Mania Rating Scale-Parent Version were completed. This study shows that PBD comorbidity in children with ASD involves a highly episodic course, with manic episodes, subsyndromal symptoms and interepisodic periods commonly being described in the manic symptom profile of these children. These findings need to be repeated with large samples, together with controlled studies concerning therapeutic interventions directed toward PBD comorbidity in children with ASD.